Connecting to regional markets? Transport, logistics services and international transit challenges for Central Asian food-processing firms. Issue 1 (2nd January 2016) - Coulibaly, Souleymane; Thomsen, Lotte
Abstract : Central Asian food processors face a number of constraints when they attempt to export to the region and beyond. The Central Asian economies in focus here are landlocked, and thus lack easy access to sea transport. In addition, the region's transport network was built to reinforce the interdependence of the then Soviet republics, while conflicting economic interests make cross-border cooperation difficult. Based on extensive fieldwork on infrastructure systems and firm export strategies, this paper identifies contemporary infrastructure and transportation issues within the Central Asian region, and makes a novel attempt to examine how these factors lead to challenges for local food processing producers trying to sell their products in the region and beyond.